Cognitive Models of Clinical Reasoning and Conceptual Representation - Patel, V. L.; Arocha, J. F. (Methods of Information in Medicine, 1995)
This paper presents an approach to conceptual representation, informed by theories and methods from cognitive psychology. Our investigation of clinical case comprehension and reasoning from textual information has shifted from instantiation models in which text processing is carried out through schema fitting to more dynamic models that account for how schemata are constructed by a process of construction and integration of meaning, which depends on specific situations. We give an example involving doctor-patient dialogue to illustrate this point. Nonetheless, our main approach has been propositionally-based. As we conduct research into more specific aspects of medical understanding, such as understanding of physiological systems, we have included alternative approaches, such as qualitative functional graphs. We present examples of their use in our research. These representational formalisms allow us better to capture reasoning and understanding in dynamic systems.
Keywords: Conceptual Representation; Cognitive Models; Clinical Reasoning